The work and training situation for young physicians undergoing specialty training in gynecology and obstetrics in Germany: an assessment of the status quo - Lermann, Johannes; Knabl, Julia; Neimann, Johannes; Schulte, Kevin; Proske, Kim; Schott, Sarah; Raspe, Matthias (Archives of Gynecology and Obstetrics, 2020)
Purpose: General conditions in the health-care system in Germany have changed dramatically in recent years. Factors affecting this include above all demographic change, rapid developments in diagnostic and therapeutic options, and the application of economic criteria to the health-care sector. This study aimed to establish the current status quo regarding conditions of work and training for young doctors in gynecology and obstetrics, analyze stress factors, and suggest potential improvements. Methods: Between October 2015 and March 2016, a web-based survey was carried out among residents and members of the German Society for Gynecology and Obstetrics. The electronic questionnaire comprised 65 items on seven topics. Part of the survey included the short version of a validated model of professional gratification crises for analyzing psychosocial work-related stress. Results: The analysis included a total of 391 complete datasets. Considerable negative findings in relation to psychosocial work pressure, time and organizational factors, quality of specialty training, and compatibility between work and family life and work and academic tasks were detected. A high level of psychosocial work pressure is associated with more frequent job changes, reduced working hours, poorer health among physicians, and a lower subjectively assessed quality of care. Conclusions: Greater efforts are needed from all the participants involved in patient care to achieve high-quality training and working conditions that allow physicians to work in a healthy and effective way. These aspects are all prerequisites for sustainably maximizing the resource “physician” and for ensuring high-quality patient care.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Gynecology and obstetrics; Medical specialty training; Psychosocial work pressure; Stress factors; Working conditions